Evaluation of the morphological Characteristics of broadleaf and needle leaf old trees for Use in Reforestation of forests in Ilam Province - ahmad hosseini; mostafa khoshnevis; mohammad reza jafari (تحقیقات کاربردی علوم جغرافیایی)
Old trees as the most important genetic reserves of the country have great importance and value in various aspects of ecology, forest restoration management, ecotourism and even history. In this research, after identification of the old trees in the forests of Ilam province, their morphological characteristics including DBH, trunk height, total height, crown length, min & max crown diameter, crown health, crown firmness, crown symmetry, Trunk health and trunk shape were examined. The selection of old trees was based on DBH criterion. After the forest survey, 43 old trees including 5 Petrocarya fraxinifolia, 5 Ulmus glabra, 11 Fraxinus rotundifolia, 3 Celtis caucasica, 4 Platanus orientalis, 4 Ficus carica, 7 Olea europea and 4 Cupressus sempervirens were identified. The results showed that among single-stranded trees, P. orientalis had the highest mean DBH (171 cm), total height (15.8 m) and trunk height (6 m), and among multi-stranded trees O. europea had the highest mean DBH (260 cm). P. fraxinifolia and U. glabra had the highest mean of crown length (11 m) and F. rotundifolia had the highest crown area (195 m2). The highest percentage of single-trunks belonged to the P. fraxinifolia (80%) and C. caucasica (67%). The highest percentage of healthy trunks belonged to C. sempervirens (50%) and O. europea (50%) and the highest percentage of healthy crowns belonged to P. fraxinifolia (100%), C. caucasica (100%), P. orientalis (100%), O. europea (100%) and F. carica (100%). The highest percentage of crown symmetry was belonged to C. caucasica (100%) and the highest percentage of crown freshness was belonged to P. fraxinifolia (100%), F. rotundifolia (100%), C. caucasica (100%), P. orientalis (100%), O. europea (100%) and F. carica (100%). Based on the desirable morphological characteristics of old trees, it is possible to help the strengthen and restoration of Zagros forests by producing resistant seedlings from their seeds. Key words: Old trees, Morphology, Oak forests, Ilam.